A Debt Intolerance Framework Applied to Central America, Panama and the Dominican Republic - Bannister, Geoffrey (IMF Working Papers; Working Paper ;, 2011)
This paper presents an alternative method for calculating debt targets using the debt intolerance literature of Reinhart, Rogoff, and Savastano (2003) and Reinhart and Rogoff (2009). The methodology presented improves on the previous papers by using a dynamic panel approach, correcting for endogeneity in the regressors and basing the calculation of debt targets on credit ratings, a more objective criteria. In addition the study uses a new data base on general government debt covering 120 countries over 21 years. The paper suggests a ranking of Central America, Panama, and Dominican Republic (CAPDR) countries in terms of debt intolerance - an index which could be used to further investigate the main components of debt intolerance.